PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASIA MUJUR - Isa Bella Simatupang Bella; Puspita Purba Purba; Kristofel Tigmar Purba Purba; Yovie Ernanda Ernanda (JEBIM Prima, 2022)
This study aims to determine the effect, work environment and employee performance on PT Asia Mujur. This research is a quantitative study with a questionnaire instrument distributed with a population of 60 people with a total sampling technique of 60 people. The results showed that the tcount of motivation was 1.114 > 1.672 at a significant value of 0.0270 > 0.05, so it gave the result that motivation had no effect on employee performance. The tcount value of the work environment obtained is 6.480> 1.672 at a significant value of 0.000 <0.05, it gives the result that the work environment has a positive and significant influence on employee performance. The count value of job satisfaction is 1.026 > 1.672, at a significant value of 0.309 > 0.05, it gives the result that job satisfaction has no effect on employee performance. Simultaneous test results obtained a value of 25.175 > 3.16 and a significant probability value of 0.000 < 0, 05. The coefficient of determination shows 75.8%, namely motivation, work environment and job satisfaction have an impact on employee performance, while the remaining 24.2% is influenced by testing factors that are not included in this variable.